2016
DOI: 10.1103/physrevaccelbeams.19.012001
|View full text |Cite
|
Sign up to set email alerts
|

Thermocurrents and their role in highQcavity performance

Abstract: Over the past years it became evident that the quality factor of a superconducting cavity is not only determined by its surface preparation procedure, but is also i n f l u e n c e d b y t h e w a y t h e c a v i t y i s c o o l e d d o w n . Moreover, different data sets exists, some of which indicate that a slow cool-down through the critical temperature is favourable while other data states the exact opposite. Even though there were speculations and some models about the role of thermo-currents and fluxpinn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…While the overall thermocurrent is mainly defined by the material properties and the temperatures of the two joints, previous studies have demonstrated that the magnetic field at the rf surface is strongly dependent on the temperature distribution [4,5]. Figure 2 depicts the distribution of the thermocurrent for two different temperature configurations.…”
Section: Setupmentioning
confidence: 98%
See 1 more Smart Citation
“…While the overall thermocurrent is mainly defined by the material properties and the temperatures of the two joints, previous studies have demonstrated that the magnetic field at the rf surface is strongly dependent on the temperature distribution [4,5]. Figure 2 depicts the distribution of the thermocurrent for two different temperature configurations.…”
Section: Setupmentioning
confidence: 98%
“…It has been demonstrated that large temperature differences between the two cavity (niobium) and tank (titanium) joints drive thermoelectric currents during the cool down process in a horizontal cavity test assembly or cryomodule. The currents generate a magnetic field which can get trapped during the superconducting phase transition [3][4][5]. Any asymmetry in the temperature profile is important in determining the additional surface resistance, which can be as high as 10 nΩ, thus degrading significantly the quality factor of typical cavities [6].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it was found that the size of trapped flux is affected by several different parameters, such as the cooldown conditions or material properties like RRR (residual resistivity ratio). This laid the basis for further, systematic investigations [1][2][3][4][5][6][7][8][9][10][11]. These methods have in common that the magnetic flux is observed indirectly-either by measuring its impact on the cavity performance or by measuring the impact of the incomplete Meissner transition on the ambient magnetic field or by small angle neutron scattering.…”
Section: Introductionmentioning
confidence: 99%